Hubungan Perilaku Bullying dengan Kecemasan pada Siswa SMP Negeri 26 Bandar Lampung - Anggun Istawala; Eka Trismiyana; Prima Dian Furqoni; Rahma Elliya (Universitas Malahayati Lampung, 2025)
ABSTRACT Bullying refers to behaviors in which individuals use violence to harm, insult, coerce, mentally embarrass, or exert control over others, leading to the victim being subjected to intimidating actions. According to data from the Women's Empowerment and Child Protection Service (PPPA) of Bandar Lampung City, the incidence of violence among junior high school students is ranked second, with a proportion of 36.2% or 122 children. At SMP Negeri 26 Bandar Lampung, there was a reported maximum of 11 instances of bullying behavior, with 7 of these cases associated with severe anxiety. Anxiety is an emotional state characterized by discomfort arising from uncertainty and feelings of helplessness due to unclear situations. This study aims to examine the relationship between bullying behavior and anxiety among students at SMP Negeri 26 Bandar Lampung. This research employs a quantitative approach with an analytical survey design and a cross-sectional method. The sample comprised 140 respondents, selected using stratified random sampling.The majority of participants were adolescents aged 13 years. Statistical analysis yielded a p-value of 0.000 (0.05), indicating a significant relationship between bullying behavior and anxiety. Sugesstion It is recommended that students become more actively involved in extracurricular activities at school. Engagement in positive activities is anticipated to mitigate the prevalence of bullying and reduce anxiety levels. Keywords : Bullying, Anxiety, Students ABSTRAK Bullying merupakan suatu tindakan dimana seseorang menggunakan kekerasan untuk menyakiti, menghina, menekan mempermalukan mental, dan mengontrol orang lain, sehingga korbannya menerima perlakuan dalam bentuk perilaku intimidasi. Data Dinas Pemberdayaan Perempuan dan Perlindungan Anak (PPPA) Kota Bandar Lampung menempati urutan ke-2 dengan kasus kekerasan terbanyak. pada siswa Sekolah Menengah Pertama dengan proporsi 36,2 % atau 122 anak dan di SMP Negeri 26 Bandar Lampung menunjukkan hasil perilaku bullying terbanyak 11 orang dengan kecemasan berat 7 orang.Kecemasan merupakan suatu keadaan emosi yang timbul akibat ketidaknyamanan yang dirasakan seseorang. pengalaman ketidakpastian yang disertai perasaan tidak berdaya disebabkan oleh sesuatu yang belum jelas.Diketahui hubungan Perilaku Bullying dengan kecemasan pada siswa di SMP Negeri 26 Bandar Lampung.Jenis penelitian kuantitatif Desain Survey analitik dengan pendekatan cross sectional. Sampel berjumlah 140 responden,Teknik sampel menggunakan Stratified random sampling Penelitian ini mayoritas perempuan usia madya (13 tahun) dan hasil analisis p-value 0,000 (0,05) yang berarti ada hubungan yang signifikan antara Bullying dengan Kecemasan. Saran kepada Siswa lebih aktif dalam mengikuti kegiatan ekstrakurikuler disekolah diharapkan jika siswa mengikuti kegiatan ekstrakulikuler, maka dengan adanya kegiatan yang positif diharapkan akan mengurangi tingkat kejadian perundungan disekolah. Kata Kunci : Bullying, Kecemasan, Siswa